Meta‐analysis of early adolescent self‐regulation interventions: Moderation by intervention and outcome type. Issue 2 (4th February 2022) - Murray, Desiree W.; Kurian, Jennifer; Soliday Hong, Sandra L.; Andrade, Fernanda C.
Abstract: Introduction: Self‐regulation has been identified as a highly promising target for interventions promoting broad wellbeing across development; however, there appear to be notable limitations in efficacy for early adolescents in particular. One possible reason is that the emotion regulation needs of youth have not been intentionally targeted in many interventions for this age group. The aim of this study is to advance understanding of how different intervention approaches defined from a clear theoretical model may impact different types of outcomes and with regard to different types of measures. Methods: We conducted a systematic literature review of four databases using Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines and identified 33 studies of early adolescents (aged 10–15) using five different intervention approaches that were methodologically rigorous (e.g., randomized controlled trial design with low risk of bias). Studies were conducted predominantly in North America (58%), and Western Europe (30%). Results: A two‐level mixed‐effects meta‐analysis indicated a small but significant overall intervention effect (Hedges g  = 0.12). When examined by intervention type, effects were significant only for approaches focusing predominantly on emotion regulation ( g  = 0.20), which significantly improved behavioral outcomes as well as emotional outcomes. Approaches examining cognitive regulation, parent training, physical activity, and working memory did not differ significantly from zero. Across intervention types, outcomes demonstrated the largest effects for youth report of emotional distress. Conclusion: Overall, results suggest that emotion regulation may be a critically important self‐regulation mechanism during early adolescence and demonstrates value in the use of applied theoretical frameworks to operationalize intervention approaches and outcomes.